POTENSI SIMPANAN KARBON DAN EMISI CO2 AKIBAT PENEBANGAN DI HUTAN ALAM PAPUA - Yuniawati; Dulsalam; Sarah Andini (BRIN Publishing, 2022)
Forests as a place for carbon sequestration will be a source of emissions if there are no more photosynthetic plants to store carbondioxide (CO2) gas. CO2 gases that spreads in atmosphere can affect global climate change. Uncontrolled timber harvesting innatural forests has a negative impact on the potential for carbon absorption and CO2 emissions. This study aimed to analyze thepotential for carbon storage and emission due to felling in natural forests. The research method was carried out destructively andnon-destructively using data on potential stands before felling and the potential for trees to be felled on three logging compartmentsby making nine sample observation plots (PCP) in three selected felling plots within the natural forest concession area, namely plotsnumbered CC 47, K47, and L 47. Each PCP was a rectangular plot measuring 2 ha (200 x 100 m2). The results showed thatthe natural forest stand structure in the study location formed an inverted J letter, where the stands with a diameter class of 60 cmand above had a lower stand volume than other diameter classes. Carbon storage in the stand before felling was 21.07 ton C/ha.The potential for carbon storage decreased when 144 trees were felled, resulting the reduction was 18.49 ton C/ha, causing apotential carbon emission of 67.86 tons CO2-eq. After felling, the potential for carbon storage was decreased or remained by 2.57ton C/ha so that the potential for emission in the post-felling area was 9.43 tons CO2-eq.